2022
DOI: 10.1080/21655979.2022.2059614
|View full text |Cite
|
Sign up to set email alerts
|

Hox transcript antisense RNA knockdown inhibits osteosarcoma progression by regulating the phosphoinositide 3-kinase/AKT pathway through the microRNA miR-6888-3p/spleen tyrosine kinase axis

Abstract: Long non-coding RNA HOX transcript antisense RNA (lncRNA HOTAIR) is thought to be a key regulator of the occurrence and development of osteosarcoma (OS). The expression of HOTAIR, microRNA miR-6888-3p, spleen tyrosine kinase (SYK), and phosphoinositide 3-kinase/AKT (PI3K/AKT) pathway-related proteins in OS was detected by quantitative reverse transcription-PCR (qRT-PCR) and western blotting. Changes in the proliferation and migration of OS cells were detected by Cell Counting Kit-8 (CCK-8) and transwell assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In terms of MALAT1, a study suggested that high MALAT1 expression is also associated with advanced clinicopathological features as well as poor prognosis in osteosarcoma ( 54 ), which might emerge as potential therapeutic targets in the treatment of patients with osteosarcoma. Most long non-coding RNAs could play regulatory roles in various biological processes of osteosarcoma cells through some miRNA-related axes, such as lncRNA HOTAIR ( 55 ) and lncRNA HCP5 ( 56 ). Evolutionary trends of the keywords in ncRNAs of osteosarcoma indicated that non-coding RNAs were characterized by the lack of ability to encode proteins; however, they gradually attracted great attention and became the latest research hotspots in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of MALAT1, a study suggested that high MALAT1 expression is also associated with advanced clinicopathological features as well as poor prognosis in osteosarcoma ( 54 ), which might emerge as potential therapeutic targets in the treatment of patients with osteosarcoma. Most long non-coding RNAs could play regulatory roles in various biological processes of osteosarcoma cells through some miRNA-related axes, such as lncRNA HOTAIR ( 55 ) and lncRNA HCP5 ( 56 ). Evolutionary trends of the keywords in ncRNAs of osteosarcoma indicated that non-coding RNAs were characterized by the lack of ability to encode proteins; however, they gradually attracted great attention and became the latest research hotspots in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that by overexpressing miR-101 and miR-139 ( Figure 6D ) can downregulate rock1 while causing PI3K/AKT and JAK/STAT signaling pathway inactivation, ultimately leading to the malignant behavior of osteosarcoma cells can be partially suppressed, including biological behaviors such as abnormal proliferation, migration and invasion ( 191 , 197 ). MiR-340-5p ( 165 ), miR-506-3p ( 159 ), miR-615 ( 59 ), miR-18a ( 192 ), miR-122-5p ( 193 ), miR-451a ( 26 ), miR-449a ( 172 ), miR-142 ( 199 ), miR-499a-5p ( 175 ), miR-6888-3p ( 202 ), miR-384 ( 203 ), and miR-223 ( 205 ), miR-29c-3p ( 178 ), miR-152 ( 207 ), miR-149-5p ( 180 ), miR-652 ( 212 ), miR-1224-5p ( 213 ), miR-146b-5p ( 204 ), miR-141-3p ( 209 ), miR-141 [198], miR-29b ( 187 ), and miR-223 ( 188 ) are all lowly expressed in osteosarcoma cells as tumor suppressors, and they can act directly on NRF2, RAB3D, HK2, MED27, TP53, YTHDC1, EZH2, CDK6, PPM1D, SYK, SLBP, Hsp90B1, TPX2, c-MET, Fn14, HOXA9, PLK1, PDK1, SIX1, AUF1, Spin 1, Ect2 and thus inhibit the PI3K/AKT pathway, which ultimately leads to the impact of osteosarcoma cells in proliferation, migration, invasion, apoptosis, autophagy, cell cycle, cell growth, etc., and inhibits the development of osteosarcoma and progression of osteosarcoma. In addition, miR-206 can also act on both PAX3 and MET target genes to achieve the inhibition of PI3K/AKT pathway through two pathways, so the inhibitory effect of miR-206 on osteosarcoma may be more obvious ( Figure 6E ) ( 189 ).…”
Section: Role Of Microrna/pi3k/akt Axis In Osteosarcomamentioning
confidence: 99%